FUZZY LOGIC MODEL OF WEAR CHARACTERISTIC OF SURFACE ALLOYED WITH FERROMANGANESE POWDER - Ozel, Serkan; Yalcin, Bekir; Turhan, Hueseyin; Somunkiran, Ilyas (Gazi Univ, Fac Engineering Architecture, 2008)
In this study, wear performance of cast copper alloyed with ferromanganese powder was determined by wear experiments. Surface of the specimens produced by cast copper were alloyed with 9 g ferromanganese powders using 115 A, 125 A and 140 A current intensities applied by Gas Tungsten Arc (GTA) Method. Wear experiments were carried out using different loads 20, 40 and 60 and sliding distances. The wear characteristics were measured with weight loss. Fuzzy logic model was setup according to experimental results. Current intensity, applied load and sliding distances were assigned as inputs and then wear amount was designed as output in this fuzzy logic model. Based on experimental results, system input and output membership functions were determined. Output support range was investigated in eight groups to be able to make sensitive estimates. It is found that estimated wear amount with the use of the proposed system be very close to experimental wear results thanks to regration analyses (R2 correlation values). For untested conditions wear performance characteristics could be determined with an application of the proposed fuzzy logic model of the investigated alloys.
Keywords: Surface alloying; wear; fuzzy logic